Tidal Volume in Infants with Congenital Diaphragmatic Hernia Supported with Conventional Mechanical Ventilation - Sharma, Saumya; Abubakar, Kabir M.; Keszler, Martin (American Journal of Perinatology, 2015)
Objective This study aims to test the hypothesis that the tidal volume (VT) required for maintaining eucapnia in infants with congenital diaphragmatic hernia (CDH) is not reduced to the same degree as their lung mass.Study Design Records of infants with CDH admitted to our hospital from 1997 to 2009 managed with conventional ventilation were reviewed. Demographics, ventilator settings, observed VT, respiratory rate (RR), and blood gas values pre- and postsurgery were recorded. Minute ventilation (MV) was calculated as a product of RR × VT. Only VT values with corresponding Paco2 between 35 and 60 mm Hg were included. Mean VT/kg and MV/kg were calculated for each patient. Forty term/late preterm infants ventilated for lung disease other than CDH or pulmonary hypoplasia served as controls.Results Birth weights of the 19 patients with CDH and 40 control infants were similar (3,360 ± 480 g and 3,300 ± 640 g). Mean gestational age was 38.5 ± 2 and 37.4 ± 1.5 week, p = 0.02. Infants with CDH required similar VT and MV as controls to maintain equal Paco2.Conclusions Infants with CDH require similar VT to clear their CO2 production compared with infants of similar size without pulmonary hypoplasia. These are the first reference values to guide selection of VT in infants with CDH.
Keywords: congenital diaphragmatic hernia; tidal volume; minute ventilation; mechanical ventilation